The Exposure of participative banks to changes in interest rates : Its emergence, impacts and potential measures to address them. - MEZINE Anass; YAACOUBI Abdelhak (African Scientific Journal, 2024)
Abstract The specificities of participative banks expose them, not only to traditional credit, market and operational risks, but also to risks of a unique nature. Although their mode of operation is not based on interest rate, several studies have demonstrated that participative banks are susceptible to fluctuations in market interest rates. The balance sheet structure, customer behavior, the absence of a refinancing market specific to participative banks and the shortage of sharia-compliant hedging instruments, increase their exposure to interest rate risk and make its management more complex. The objective of this paper is to provide answers to the problematic of exposure of participative banks to interest rate risk. To do this, we will adopt a theoretical approach based on a literature review, allowing on the one hand, to study the extent to which Moroccan participative banks may be impacted by changes in market reference rates, on the basis of the experience of participative banks operating in countries with a dual banking system and an underdeveloped or nonexistent Islamic financial market. Furthermore, we will illustrate the various practices and techniques developed to manage this risk. We intend to initially investigate this issue, its potential effects, and the various measurement and management techniques that can be employed to mitigate it. And subsequently, to present the best management practices that Moroccan participative banks, considering their specificities, can implement with the aim of addressing their exposure to such risk. Our study states that Moroccan participative banks are exposed to an extrinsic interest rate risk due to their operational environment. Despite their exposure, they lack the same flexibility as conventional banks when it comes to managing the potential impact on their financial situation. The recommendations provided in this paper focus notably on innovation and financial engineering in Sharia-compliant hedging financial instruments, the implementation of a reserve policy for risk management, and financial market education. Keywords : Participative banks, interest rate risk, sensitivity, duration, ALM Résumé Les spécificités des banques participatives les exposent, en plus des risques classiques de crédit, marché et opérationnel, à des risques de nature unique. Bien que leur mode de fonctionnement est excepte du taux d’intérêt, plusieurs études réalisées ont démontré que les banques participatives se trouvent exposées aux fluctuations des taux d’intérêt du marché. La structure bilancielle, le comportement de la clientèle, l’absence d’un marché de refinancement propre aux banques participatives et la pénurie des instruments de couverture conformes à la charia, favorisent davantage leur exposition au risque de taux d’intérêt et rendent sa gestion plus complexe. L’objectif du présent article est d’apporter des éléments de réponse à la problématique de l’exposition des banques participatives au risque de taux d’intérêt. Pour ce faire, nous utilisons une approche théorique basée sur une revue de littérature, permettant d’une part, d’étudier dans quelles mesures les banques participatives marocaines pourront être impactées par les variations des taux de référence du marché, en se basant sur l’expérience des banques participatives exerçant dans des pays caractérisés par un écosystème dual et un marché financier islamique sous développé ou inexistant. Et d’autre part, de présenter les diverses pratiques et techniques développées pour gérer ce risque. Nous nous proposons d’étudier, dans un premier temps, cette problématique, ses effets potentiels et les différentes techniques de mesure et de gestion pouvant être utilisées pour en faire face. Et de présenter, par la suite, les bonnes pratiques de gestion que les banques participatives marocaines, tenant compte leurs spécificités, peuvent mettre en place dans l’objectif d’atténuer leur exposition audit risque. Notre étude affirme que les banques participatives Marocaines se voient exposées à un risque de taux d’intérêt extrinsèque suite notamment à l’environnement dans lequel elles exercent. Toutefois, elles n’ont pas la même souplesse que les banques conventionnelles pour gérer ses répercussions potentielles sur leur situation financière. Les recommandations apportées dans cet article portent notamment sur l’innovation et l’ingénierie financière en matière des instruments financiers de couverture conformes à la charia, la mise en place d’une politique de réserve pour la gestion du risque ainsi que l’éducation financière du marché. Mots clés : Banques participatives, risque de taux d’intérêt, sensibilité, duration, ALM